The Kingdom of God and Christian Unity and Fellowship: Romans 14:17 in Context - Corneliu Constantineanu (Kairos (English Ed.), 2008)
Beginning with a reminder of the centrality of the concept of the Kingdom of God for Jesus’ ministry and teaching and for the early church, the presentation attempts to show that, despite some contrary voices, the notion of the Kingdom of God is still a very useful and significant category for the present Christian ethical reflection in general, and for Christian unity and fellowship in particular. Being given such a specific and limited purpose for the presentation, after some brief but necessary clarifications about the meaning of the Kingdom of God (sovereignty/reign/ realm – present/future – inward/external – transcendent/immanent), the article offers an exploration of several ways in which the concept of the Kingdom of God is significant for Christian unity and fellowship, from a New Testament/Pauline perspective.